Condensate banking removal: study on ultrasonic amplitude effect - Ainuddin, A. (Springer Science and Business Media Deutschland GmbH, 2021)
Hydrocarbons in a gas condensate reservoir consist of a wide variety of molecules which will react varyingly with the change of pressure inside the reservoir and wellbore. The presence of heavier ended hydrocarbons such as C5 and above, condensate banking will occur as pressure depletes. Pressure drop below dew point pressure causes condensate buildup which will give a negative impact in the productivity index of a gas condensate reservoir. Gas condensate reservoirs experience liquid drop out when pressure depletion reaches below dew point pressure. This occurrence will eventually cause condensate banking over time of production where condensate builds up in pore spaces of near-wellbore formations. Due to increase in condensate saturation, gas mobility is reduced and causes reduction of recoverable hydrocarbons. Instead of remediating production loss by using unsustainable recovery techniques, sonication is used to assist the natural flow of a gas condensate reservoir. This study aims to evaluate the effects of various ultrasonic amplitudes on condensate removal in a heterogenous glass pack in flowing conditions with varying exposure durations. Experiments were conducted by using n-Decane and a glass pack to represent condensate banking and near-wellbore area. Carbon dioxide was flowed through the pack to represent flowing gas from the reservoir after sonication of 10, 50 and 100 amplitudes (20Â kHz and 20 Watts). Analysis of results shows recovery of up to 17.36 and an areal sweep efficiency increase in 24.33 after sonication of 100 amplitude for 120Â min due to reduction in viscosity. It was concluded that sweeping efficiency and reciprocal mobility ratio are increased with sonication of 100 amplitude for 120Â min. This indicates that mobility of n-Decane is improved after sonication to allow higher hydrocarbon liquid production. Insights into the aspects of the mechanical wave are expected to contribute to a better understanding of tuning the sonic wave, to deliver remarkable results in a closed solid and fluid system. This form of IOR has not only proved to be an effective method to increase productivity in gas condensate wells, but it is also an environmentally sustainable and cost-effective method. Â© 2021, The Author(s).